THERMOMAGNETIC REACTIVE ETHYLENE GLYCOL-METALLIC NANOFLUID TRANSPORT FROM A CONVECTIVELY HEATED POROUS SURFACE WITH OHMIC DISSIPATION, HEAT SOURCE, THERMOPHORESIS AND BROWNIAN MOTION EFFECTS. (3rd September 2022) - Shamshuddin, MD.; Mabood, Fazle; Bég, O. Anwar
ABSTRACT: The objective of this study is to develop a mathematical model for chemically reacting magnetic nanofluid flow with thermophoretic diffusion, Brownian motion and Ohmic magnetic heating in a Darcian permeable regime. The current flow model also considers a number of different nanofluid types i.e. Cu, Ag and Au nanoparticles with base fluid ethylene glycol. Effectively a nanoscale formulation combining the Buongiorno two-component model with the Tiwari-Das model is deployed so that a nanoparticle species diffusion equation is also included as well as material properties for specific nanoparticles and base fluids. By means of similarity transformations, non-linear dimensionless ordinary differential equations are derived (from the original partial differential equations) and solved numerically by means of Runge-Kutta-Fehlberg-fourth fifth order method. The effect of emerging parameters on velocity, temperature, concentration, skin friction, Nusselt number and Sherwood number profiles is visualized graphically. Validation with earlier studies is included. The computations show that temperatures are suppressed with greater thermal Grashof and Biot numbers. Nanoparticle-concentrations are strongly diminished with increasing reactive species and Lewis number, whereas Sherwood number is elevated with stronger chemical reaction effect. The study is relevant to magnetic nanomaterials processing.